XIX әсирдиң ақыры XX әсир басларында Қарақалпақстандағы мәдений-тарийхый шараят ҳәм жәдидшилик ағартыўшылық ҳәрекети - Сейтмуратов, Қ (SCIENCE and SOCIETY, 2024)
The article examines the cultural and historical conditions of Karakalpakstan in the second half of the 19th - early 20th centuries, the emergence of the Jadid movement, reforms in the field of education, the creation of Jadid schools, and the publication of new generation textbooks.
Keywords: education; upbringing; Jadid movement; Jadid school; textbook; cultural and historical heritage